7 - Mass médias et figures du religieux islamique au Mali : entre négociation et appropriation de l’espace public: by Naffet Keïta - Keita, Naffet (Africa Development, 2021)
Since 11 September 2001, a divide has grown up between opinions and a certain form of practice of Islam. Some do not hesitate to talk about a ‘war of civilisations’. In this context, today’s Mali appears as a playing field for competition between divergent religious currents. The proliferation of religious associations following 26 March 1991 reflects the development of a ‘chapel or micro-religion’ phenomenon that complicates not only interfaith relations, but also relations between religions and the state. The state is faced with an increasingly complex religious environment with widely varied means of infiltration, expansion and multiple manifes- tations, but we can chiefly take note of the social action of NGOs and associations (national and international), which relays the action of reli- gious institutions. The new manifestations of religion have benefitted from the technical and technological progress of the dawning century (development of means of transportation and communications technologies) and the ex- tension of democratic rights and freedoms. The dynamics underway are translated by the formation of divergent religious groups, or even sects, some of which, due to their rejection of any form of social compromise, are sources of conflict. The tensions between the different currents are sometimes heightened by external influences or sociological and eco- nomic antagonisms. Attempts to politicize religion also contribute to these tensions.